Probability of error of OFDM systems with carrier frequency offset in frequency-selective fading channels - Rugini, L.; Banelli, P.; Cacopardi, S. (2004 IEEE Itnernational Conference on Communications, 2004)
This paper presents an analytical approach to evaluate the error probability of orthogonal frequency-division multiplexing (OFDM) systems subject to carrier frequency offset (CFO) in frequency-selective channels, characterized by Rayleigh or Rician fading. By exploiting the Gaussian approximation of the intercarrier interference (ICI), we show that the bit-error rate (BER) for quadrature amplitude modulation (QAM) can be expressed by the sum of few integrals, whose number depends on the constellation size. Each integral can be evaluated numerically, or, in Rayleigh fading, by using a series expansion that involves generalized hypergeometric functions. Simulation results illustrate that the theoretical analysis is quite accurate, especially for Rayleigh channels.